Descripción y funcionamiento de una cámara de transformación. - Armijos Minga, Carlos Alberto (2011)
The overall processing chambers should be located as close as possible to the primary network of public service should be easily accessible and have sufficient amplitude to maintain the minimum distances between live parts allowed both between them and land in such a way to allow access to qualified personnel to perform preventive and corrective maintenance of equipment installed. The construction of a processing chamber depends on the area and facilities to provide the land, may be these, external or semi-underground. The design and construction of chambers transformation takes into account two important global aspects, the civil and electrical. Electrical equipment for use in a processing chamber are well defined, as being the transformer core team the other teams are complementary to this, because it is protection on both the low and in that of high transformer and accessory chosen at the beginning and end of the cable used to power the same The purpose of electrical protection is: to reduce to a minimum number of service interruptions, protect from damage during any type of equipment failure, and saves time and money on troubleshooting and service restoration The selection of the transformer depends on several determinants such as the processor's capacity is a direct function of the initial and future loads to be served, the voltage level, level of insulation, insulation, type of insulation is this internal or external, etc. . In some cases we must also take into account the allowable noise level.